Poor Claims Settlement And Demand For Insurance Policies In Nigeria - Momoh, Omowumi Ayoni; Oyetunji, Oyefemi Ismail O. (Advances in Social Sciences Research Journal, 2021)
This study investigates the poor claims settlement and demand for insurance policies in Nigeria to provide empirical evidence which would assist not only the insurance companies but also the policymakers by using these findings to design future insurance services and policies that can be geared towards promoting insurance market development. The population focused in the study included few licensed insurance firms in Nigeria. This is due to the fact that they dominate and control the larger interest in the market share. Primary data was used for this study through well-structured questionnaire. Chi- squared statistics and correlation with the tabulated contingency table on the basis of an assumptions were employed. The results show that poor claim settlement has significant effect on demand for Insurance policies in Nigeria and that there is long term and significant relationship between poor claim settlement and demand for insurance policies in Nigeria. The study therefore, recommends that insurance industry should be redefined through appropriate Acts, introducing competitions and innovations in the services so as to compete effectively and meet consumer needs by dealing with changing expectations of policyholders so as to ensure that satisfaction of all the parties are guaranteed.